Allergenic components of the mRNA‐1273 vaccine for COVID‐19: Possible involvement of polyethylene glycol and IgG‐mediated complement activation - Klimek, Ludger; Novak, Natalija; Cabanillas, Beatriz; Jutel, Marek; Bousquet, Jean; Akdis, Cezmi A. (Allergy (Copenhagen), 2021)
Following the emergency use authorization of the mRNA‐1273 vaccine on the 18th of December 2020, two mRNA vaccines are in current use for the prevention of coronavirus disease 2019 (COVID‐19). For both mRNA vaccines, the phase III pivotal trials excluded individuals with a history of allergy to vaccine components. Immediately after the initiation of vaccination in the United Kingdom, Canada, and the United States, anaphylactic reactions were reported. While the culprit trigger requires investigation, initial reports suggested the excipient polyethylene glycol 2000 (PEG‐2000)—contained in both vaccines as the PEG‐micellar carrier system—as the potential culprit. Surface PEG chains form a hydrate shell to increase stability and prevent opsonization. Allergic reactions to such PEGylated lipids can be IgE‐mediated, but may also result from complement activation‐related pseudoallergy (CARPA) that has been described in similar liposomes. In addition, mRNA‐1273 also contains tromethamine (trometamol), which has been reported to cause anaphylaxis to substances such as gadolinium‐based contrast media. Skin prick, intradermal and epicutaneous tests, in vitro sIgE assessment, evaluation of sIgG/IgM, and basophil activation tests are being used to demonstrate allergic reactions to various components of the vaccines.